Hunting the dinosaurs and other prehistoric animals - Dixon, Dougal; Burton, Janel; Male, Alan; Kirk, Steve (Milwaukee : G. Stevens Pub., 1987)
Examines how paleontologists discover, study, classify, reconstruct, and restore the fossil remains of many kinds of dinosaurs.
"First published ... in the United States of America, under the title Time exposure, by Beauford Books, New York, 1984"--P. [2].
Includes index.
Bibliography: p. 29.
Keywords: Paleontology; Dinosaurs; Paleontology; Dinosaurs; Fossils